Assessment of Health Related Quality of Life in Indian Generalized Anxiety Disorder Patients - Rishi Kapoor Poddar, Piyush Mittal (South Eastern European Journal of Public Health, 2025)
Introduction Quality of life (QoL) is a broad concept that takes into consideration of both health related and non-health related aspects of life. Objective of the study wasto assess QoL in patients suffering from generalized anxiety disorder (GAD). Methods Thiswas a single-center prospective observational study. The inclusion criteria were patients with GAD, both genders, patients with age group 18-60 years, and patients willing to participate. A total of 352 patients were enrolled in the study and analysed at the baseline visit. Health-related quality of life (HRQoL) data were collected for patients with GAD using the Short Form-12 Health Survey-version 2 (SF-12v2) and EuroQoL-5 Dimension (EQ-5D-5L) questionnaires. Results The mean scores for Physical Component Summary (PCS-12) and Mental Component Summary (MCS-12) in study were 47.68±5.99 and 36.32±4.78 respectively.It was observed that variables are generally associated with lower scores on MCS-12 than on PCS-12 in the analysis of the variables.The health state and utility score of female patients was lower than that of male patients in EQ-5D-5L. Conclusion GAD has potential to decrease HRQoLsignificantly by affecting both physical and mental health status of the patients in SF-12v2in addition tomobility, self-care, usual activities, pain/discomfort, and anxiety/depression in EQ-5D-5L.